Habituation of the cardiovascular responses to restraint stress in male rats: influence of length, frequency and number of aversive sessions - Benini, Ricardo [UNESP]; Oliveira, Leandro A. [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Crestani, Carlos C. [UNESP] (Taylor & Francis, 2019)
Habituation of cardiovascular responses upon repeated exposure to stress is controversial. Hence, we hypothesized that habituation of cardiovascular stress responses is influenced by length, frequency, and number of stress sessions in male Wistar rats. Blood pressure and heart rate were recorded via femoral artery catheterization and the tail cutaneous temperature was evaluated using a thermal imager. We observed a faster return of heart rate to baseline values during the post-stress period of the 10th daily session in rats subjected to either 60 (n = 8) or 120 min (n = 7), but not 30 min (n = 7), of restraint. Daily sessions of 120 min also decreased blood pressure during the recovery of the 10th session. The faster return of heart rate to baseline values during the post-stress period at the 10th session in rats exposed to daily 60 min sessions (n = 9) was not identified at the 5th (n = 9) and 20th (n = 9) sessions. Regarding frequency, the tachycardia during the 10th session was enhanced in rats subjected to 60 min of restraint presented every other day (n = 9) and decreased in rats subjected to a protocol of five daily sessions followed by two resting days (n = 9). Thirty-minute sessions of restraint presented twice a day (n = 9) and a protocol of three daily sessions followed by a resting day (n = 9) did not affect the restraint-evoked cardiovascular responses at the 10th session. These results provide evidence of habituation of the cardiovascular responses upon repeated exposure to restraint stress, which is dependent on length, frequency, and number of trials. Lay summary Cardiovascular responses decrease upon repeated exposure to restraint stress. The decrease in cardiovascular stress responses is observed as a faster return to basal values during the post-stress period. The cardiovascular stress response decrease (habituation to stress) is dependent on the length, frequency, and number of stress sessions.
Keywords: Adaptation; blood pressure; heart rate; neuroendocrine responses; restraint; sympathetic activity